Effect of Levodopa on Reward and Impulsivity in a Rat Model of Parkinson’s Disease - Carvalho, Miguel M.; Campos, Filipa L.; Marques, Mariana; Soares-Cunha, Carina; Kokras, Nikolaos; Dalla, Christina; Leite-Almeida, Hugo; Sousa, Nuno; Salgado, António J. (Frontiers in Behavioral Neuroscience, 2017)
The use of dopamine replacement therapies (DRT) in the treatment of Parkinson’s disease (PD) can lead to the development of dopamine dysregulation syndrome (DDS) and impulse control disorders (ICD), behavioral disturbances characterized by compulsive DRT self-medication and development of impulsive behaviors. However, the mechanisms behind these disturbances are poorly understood. In animal models of PD, the assessment of the rewarding properties of levodopa (LD), one of the most common drugs used in PD, has produced conflicting results, and its ability to promote increased impulsivity is still understudied. Moreover, it is unclear whether acute and chronic LD therapy differently affects reward and impulsivity. In this study we aimed at assessing, in an animal model of PD with bilateral mesostriatal and mesocorticolimbic degeneration, the behavioral effects of LD therapy regarding reward and impulsivity. Animals with either sham or 6-hydroxydopamine-induced bilateral lesions in the substantia nigra pars compacta (SNc) and ventral tegmental area (VTA) were exposed to acute and chronic LD treatment. We used the conditioned place preference (CPP) paradigm to evaluate the rewarding effects of LD, whereas impulsive behavior was measured with the variable delay-to-signal (VDS) task. Correlation analyses between behavioral measurements of reward or impulsivity and lesion extent in SNc/VTA were performed to pinpoint possible anatomical links of LD-induced behavioral changes. We show that LD, particularly when administered chronically, caused the development of impulsive-like behaviors in 6-OHDA-lesioned animals in the VDS. However, neither acute or chronic LD administration had rewarding effects in 6-OHDA-lesioned animals in the CPP. Our results show that in a bilateral rat model of PD, LD leads to the development of impulsive behaviors, strengthening the association between DRT and DDS/ICD in PD.